2018
DOI: 10.1017/iop.2018.83
|View full text |Cite
|
Sign up to set email alerts
|

Recommended Practices for Academics to Initiate and Manage Research Partnerships With Organizations

Abstract: Although academics can receive considerable training in selecting appropriate research designs, types of data to collect, and methods for analyzing data, as well as guidance on preparing scholarly manuscripts, there is a dearth of information on how to initiate and manage partnerships with organizations in order to conduct high-quality applied research, particularly when the research is quantitative in nature. In this article, we provide our own experience-based insights and recommendations to help academics m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 23 publications
3
34
0
Order By: Relevance
“…Stories are, at the core, retellings of real-life experiences (Schank & Berman, 2002). Relatedly, Lapierre et al (2018) suggested that should "refer to any previous experience in implementing valuable change" (p. 560) as a way to indicate one's credentials and expertise. Stories are particularly useful from a sales perspective.…”
Section: Story Tellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Stories are, at the core, retellings of real-life experiences (Schank & Berman, 2002). Relatedly, Lapierre et al (2018) suggested that should "refer to any previous experience in implementing valuable change" (p. 560) as a way to indicate one's credentials and expertise. Stories are particularly useful from a sales perspective.…”
Section: Story Tellingmentioning
confidence: 99%
“…In addition to the suggestions made by the authors of the focal article (Lapierre et al, 2018), it is also important for academics to market themselves and keep their information up to date. As a practitioner, I sometimes end up…”
Section: Maintain a Web Presence So Practitioners Can Find Youmentioning
confidence: 99%
“…Other partnerships have been less fruitful, largely because both science and organizations are messy and unpredictable. But no matter the outcome, nearly all of our partnerships have come about in the same way-a way overlooked by the authors in their article (Lapierre et al, 2018).…”
Section: Googlementioning
confidence: 99%
“…The focal article (Lapierre et al, 2018) highlights many good suggestions but only briefly mentions partnering with an academically trained internal industrial and organizational (I-O) practitioner. We believe beginning a partnership with a similarly trained ally well-versed through training in academic language and through experience in "business speak" will yield a stronger end result.…”
mentioning
confidence: 99%